Anatomical and Morphometric Study of Human Skull Base Foramina in Indians: Clinical and Forensic Implications - Patel, Dr Ajay Kumar; Kumar, Dr Rajesh; Patel, Dr Rashmi Bala (Anatomical and Morphometric Study of Human Skull Base Foramina in Indians: Clinical and Forensic Implications, 2025)
The present work elucidates the anatomical and morphometric evaluation of human skull base foramina in the Indian population. The investigation was conducted in two different study groups, which consisted of thirty dry skulls and CT scans of thirty adult patients. The observations recorded in these two distinct study groups were discussed in the light of previous respective studies. The study provided information about anatomical variants and dimensions of individual skull base foramina. It became evident that the dimensions of individual foramina displayed a wide range. Statistical analysis was performed to explore any significant difference in the mean dimensions between left and right-sided foramina. The anteroposterior dimension of the jugular foramen exhibited a significant difference between the two sides in dry skulls as well as in CT scans of patients. Besides the individual foramina anatomy, one of the highlights of the current study is the localisation of skull base foramina with respect to specific osseous landmarks. The distances between foramina and osseous landmarks also displayed a wide range. The statistical analysis of our results revealed that there was a significant difference between the left and right-sided values of the mean distance of foramen spinosum to infratemporal crest in dry skulls, as well as in CT scans of patients. A detailed review of literature revealed that the assessment of interforaminal measurements of the skull base has been relatively less explored. The results of the current study were analysed statistically, and it revealed that many of the average values of interforaminal measurements in dry skulls displayed significant differences between left and right sides. It is expected that the results of the present study would be useful for Radiologists and Neurosurgeons and also serve as an anatomical reference for researchers.